2014
DOI: 10.1021/nl5032293
|View full text |Cite
|
Sign up to set email alerts
|

Effective Passivation of Exfoliated Black Phosphorus Transistors against Ambient Degradation

Abstract: Unencapsulated, exfoliated black phosphorus (BP) flakes are found to chemically degrade upon exposure to ambient conditions. Atomic force microscopy, electrostatic force microscopy, transmission electron microscopy, X-ray photoelectron spectroscopy, and Fourier transform infrared spectroscopy are employed to characterize the structure and chemistry of the degradation process, suggesting that O2 saturated H2O irreversibly reacts with BP to form oxidized phosphorus species. This interpretation is further support… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

66
1,486
1
10

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,374 publications
(1,584 citation statements)
references
References 47 publications
66
1,486
1
10
Order By: Relevance
“…The studies of Wood et al36 confirmed that the irreversible reaction of BP with O 2 ‐saturated H 2 O was responsible for the oxidized phosphorus species (PO x ), thereby providing an explanation for the structure and chemistry of degradation process 54, 216, 228. They found small topographic protrusions (bubbles) above the plane of the BP flakes shortly after exfoliation, whereas the bubble density and the height of the bubbles increased after 1 day of ambient exposure.…”
Section: Ways To Protect Phosphorene and Effective Passivationmentioning
confidence: 97%
See 2 more Smart Citations
“…The studies of Wood et al36 confirmed that the irreversible reaction of BP with O 2 ‐saturated H 2 O was responsible for the oxidized phosphorus species (PO x ), thereby providing an explanation for the structure and chemistry of degradation process 54, 216, 228. They found small topographic protrusions (bubbles) above the plane of the BP flakes shortly after exfoliation, whereas the bubble density and the height of the bubbles increased after 1 day of ambient exposure.…”
Section: Ways To Protect Phosphorene and Effective Passivationmentioning
confidence: 97%
“…The LPE of BP becomes problematic due to the degradation caused by the instability of BP in oxygen or water and stabilization is required 35, 36, 156. The encapsulation of BP was proposed as a possible solution to protect its reaction with environmental species 36, 220.…”
Section: Ways To Protect Phosphorene and Effective Passivationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it has been revealed that BP is very reactive to oxygen and water,[[qv: 4b,10]] resulting in compositional and physical changes of BP 11. The lack of water‐ and air‐stability under ambient conditions hinders its potential biomedical applications.…”
mentioning
confidence: 99%
“…The individual layers of BP exhibit a honeycomb structure differing from that of graphene in that it has a marked puckering of the sp 3 P atoms with an AB stacking structure driven by van der Waals interactions (Scheme 1). 3, 4 BP has attracted enormous attention owing to its high p‐type charge carrier mobility up to around 6000 cm 2  V −1  s −1 and its tunable direct band gap ranging from about 0.3 eV for bulk to approximately 2 eV for monolayers 2, 9, 10, 11, 12, 13, 14, 15, 16. It has recently been predicted that the electronic properties of BP can be modulated by strain or electric field 17, 18.…”
mentioning
confidence: 99%